Team‐level human resource attributions and performance. (6th November 2020) - Fan, Di; Huang, Yufang; Timming, Andrew R.
Abstract: Drawing on attribution theory, this study explores the relationship between team‐level human resource attributions (HRAs) and team performance, and explains how transformational leadership moderates this relationship. The data were collected from leaders and subordinates across 77 work teams, for a total of 708 participants employed in seven manufacturing and service organizations in China. The study finds that the relationship between commitment‐focused team‐level HRAs and team performance is mediated by team engagement, and that self‐awareness of transformational leadership significantly strengthens the positive relationship between these variables. However, parallel moderated mediation relationships are not evident between control‐focused team‐level HRAs and team performance. The study is among the first to explore team‐level HRAs and contributes to the scholarly debates on the role of attributions in explaining the so‐called 'black box' between HRM and performance.